An autopsy-based study on developing standards for estimation of stature from percutaneous length of femur in female population of Madhya Pradesh, India - Mohit, Shrivastava; Pramendra Singh, Thakur; Bajrang Kumar, Singh; Sunil, Soni; Devesh, Pateria (Journal of Indian Academy of Forensic Medicine, 2021)
Identification of an individual is very important in criminal cases like assault, murder, rape, disputed paternity, impersonation etc. and in civil cases like marriage, inheritance, disputed sex, etc. Identification of isolated extremities is an issue of great significance and plays a vital role in the investigation of the identity of victims in mass disasters and fatal assaults. The aim of the present study was to find the correlation between anthropometry of percutaneous length of femur and stature in females and to derive a regression equation formula and multiplication factor to estimate the stature from percutaneous length of femur anthropometry in the Central India region (M.P.). This cross-sectional study was carried out on 250 deceased females of age between 20-60 years, brought for postmortem examination to the mortuary of Forensic Medicine Department, M.G.M. Medical College and M.Y. Hospital, Indore (M.P.). The mean right and left percutaneous femoral length was 38.57 ± 1.70 cm and 38.57 ± 1.70 cm, respectively, whereas the mean stature was found to be 158.27 ± 5.68 cm. In this study, the maximum stature in females was found to be 172.0 cm and the minimum stature was found to be 143.80 cm. The correlation between percutaneous femoral length and stature was found to be positively correlated and the association was highly significant. The multiplication factor for percutaneous femoral length was found to be 4.10. Multiplication factors become essential in cases of forensic analysis when only limb or fragmented body part with soft tissue is available for analysis.